2008
DOI: 10.1111/j.1753-1411.2008.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Perceptions and Patterns of Cigarette and Alcohol Use among College Students in Vietnam

Abstract: This empirical study was conducted in the Socialist Republic of Vietnam to investigate crosssectionally the influences of sociocultural contexts on the patterns of addictive substance use cigarette, alcohol, and illicit drugs. A sample of 202 monolingual adults who were enrolled in college courses at the University of Hanoi in Vietnam responded to a self-reported questionnaire in their native language on the frequency, quantity, and occasions of addictive behavior. The project staff were fluent in English and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…30 Central role of cigarette smoking and alcohol use was found in the peer socialization and relationship building among college students in Vietnam as well. 31 In China, the major reasons behind smoking were belief that one looks elegant while smoking and trying to be fashionable. 32 This type of view was reflected among students in our study also.…”
Section: Page: 99mentioning
confidence: 99%
“…30 Central role of cigarette smoking and alcohol use was found in the peer socialization and relationship building among college students in Vietnam as well. 31 In China, the major reasons behind smoking were belief that one looks elegant while smoking and trying to be fashionable. 32 This type of view was reflected among students in our study also.…”
Section: Page: 99mentioning
confidence: 99%
“…Previous studies showed that the culture of smoking among Vietnamese adults seems dominated by males. 35,36 We may see that the Confucian code may have a strong influence on male behaviors in the society, resulting in high smoking rates in males than females. 37 According to the WHO, in 2010, prevalence of smoking among male in Vietnam was especially high at 47.4%.…”
Section: Discussionmentioning
confidence: 99%